ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH MERGER PADA PD BPR BKK PURWODADI - Suwardi ,- (Value Added : Majalah Ekonomi dan Bisnis, 2008)
It was interesting to observe the phenomenon of merger as  a managerial decision on BPR BKK Purwodadi. The research is aimed to study wether the merger has significant impact on the financial performance of BPR BKK in Purwodadi. The impact is meausured by comparing bank financial performance prior to and after the merger. In this  research, proxy for bank financial performance uses several ratios, such as  Net Interest Margin (NIM), Operational Cost and Operational Revenue Ratio , Return on Assets (ROA), Non Performing Loans (NPL) and Loans to Deposit Ratio (LDR). According the theory of mergers, one of the main obyektives that the firm performs merger is to use their economies of scale and scope (Koch & Mac Donald, 2002 p. 902), to  increase of their assets, cost efficiency, sales and return (ROA). In Indonesia the merger among BBD, BDN, EXIM Bank and BAPINDO, has shown significant, and  in the financial performances are better than those prior to the merger of CAR, RORA and LDR but insignificant are better on  financial performance in terms of NIM, ROA and Operation Cost and Operational Revenue Ratio (Kuncoro, 2002 p. 412 and 447). Solikhah & Payamta (2001) with their research, found that the banks were merged seem to big  and the merger and acquisition are only for the sake of political interest. This research is conducted to obtain the facts, whether their financial performances after the merger are better or worse than those prior to the merger.The data are then  processed and to analyzed to obtain guidance for the managerial policies, so that the company of bank has  competitief advantages. Differences tests being  used are Wilcoxon Test and T-test  involving 18 branches of PD BPR BKK Purwodadi during the period of 4 financial years which end in 2004, 2005, 2006 and 2007 so that there is an adequate period of 36 months financials performance prior to and after the merger. The research with Wilcoxon Test  found that there significant differences in terms of  NIM and LDR but no significant differences in terms of  BOPO, NPL and LDR. While the result T-test found that there is  no efficiency for NIM and LDR, though BOPO, ROA and NPL are better than those prior to the merger. Key words: financial performaced, merger, Wilcoxon’s Signed Rank Test, T-test, NIM, BOPO, ROA, NPL and LDR.